Co-catalyzed reductive cyclization of azido and cyano substituted alpha,beta-unsaturated esters with NaBH4: enantioselective synthesis of (R)-baclofen and (R)-rolipram - Paraskar, A. S.; Sudalai, A. (Tetrahedron, 2006)
Sodium borohydride in combination with a catalytic amount of CoCl, has been found to be an excellent catalytic system in reductive cyclizations of suitably substituted azido and cyano groups of alpha,beta-unsaturated esters to afford gamma and delta-lactams in high yields. The process has been demonstrated for the enantioselective synthesis of (R)-baclofen, (R)-rolipram, and (R)-4-fluorophenylpiperidinone, a key intermediate for (-)-paroxetine. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Asymmetric synthesis; cobalt chloride; gamma and delta-lactams; reduction; sodium borohydride

Asymmetric synthesis of (R)-(-)-baclofen via asymmetric dihydroxylation - Thakur, V. V.; Paraskar, A. S.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2007)
A short and efficient asymmetric synthesis of (R)-(-)-baclofen, a selective GABA(B) agonist has been described with an overall yield of 14% and 85% ee. The Os-catalyzed Sharpless asymmetric dihydroxylation of alpha,beta-unsaturated olefin constitutes the key step in introducing stereogenic centers into the molecule.
Keywords: asymmetric dihydroxylation; baclofen; cyclic sulfate; gamma-aminobutyric acid; Parkinsons' disease